ALLOGENEIC BONE MARROW TRANSPLANTATION IN TWO HIV-1 INFECTED PATIENTS SHOWS NO DETECTABLE HIV-1 RNA OR DNA, AND A PROFOUND REDUCTION IN HIV-1 ANTIBODIES. (February 2015) - Koelsch, K. K.; Hey-Cunningham, W. J.; Sasson, S. C.; Pearson, C.; Xu, Y.; Bailey, M.; Marks, K. H.; Hiener, B. M.; Palmer, S.; Zaunders, J. J.; Post, J. J.; Milliken, S. T.; et al.
Abstract : Aims: Two HIV-1 infected patients were studied post-haematopoietic stem cell transplant (HSCT) to determine effects on the viral reservoir. Methods: HIV-1 Ag/Ab was measured by chemiluminescence microparticle immunoassay (CMIA) and western blot (WB). Specific CD4+T-cell responses were measured by CD25/CD134 up-regulation. HIV-1 RNA was measured in serum and HIV-1 DNA was measured in peripheral blood mononuclear cells (PBMCs) and CD4+T-cells by PCR. CCR5 phenotype in PBMC was determined by PCR. Results: Patient A and B underwent HSCT for non-Hodgkin's lymphoma and acute myeloid leukemia, respectively. Both remained on antiretroviral therapy. Patient A experienced systemic graft-versus-host disease (GVHD), whereas Patient B developed skin GVHD. Patient A was heterozygous for the CCR5Δ32 mutation and Patient B was wild-type. Following HSCT, both patients had undetectable HIV-1 RNA in plasma, and undetectable HIV-1 DNA in PBMCs and CD4+T-cells. Antigen-specific CD4+T-cell responses were absent. Pre-transplant, Ag/Abs to HIV-1 was detectable. Post-transplant, patients had low-level Ag/Abs on CMIA, but trace (Patient A) and absent (Patient B) antibody by WB. Conclusion: HSCT reduced the HIV-1 reservoir size in these two patients with undetectable HIV-1 RNA in serum and DNA in PBMC/CD4+T-cells and absent antigen-specific CD4+T-cell responses. A profound reduction in Ab to HIV was demonstrated in both patients by WB.